Rediscovery of Robert Wight’s Tephrosia fusca (Fabaceae: Papilionoideae) from India - Krishnaraj, Moothedathu Venugopalan Nair; Mohanan, Narayanan Nair; Davis, Thomson (Phytotaxa, 2013)
Tephrosia fusca is rediscovered from southern part of Western Ghats, India, after 178 years. The complete description ofthe species is provided along with illustrations. A lectotype is also designated.